Inclusive education for students with intellectual disabilities - Craven, Rhonda G. (International advances in education., 2015)
As a social justice endeavor, one of the goals of inclusive education is to bolster the education of all students by promoting equal opportunities for all, and investing sufficient support, curriculum and pedagogy that cultivates high self-concepts, emphasizes students' strengths rather than weaknesses, and assists students to reach their optimal potential to make a contribution to society. Dedicated to the identification of international strategies to achieve this goal, Inclusive Education for Students with Intellectual Disabilities presents examples of theory, research, policy, and practice that will advance our understanding of how best to educate and more generally structure educational environments to promote social justice and equity. Importantly, this discussion transcends research methodology, context, and geographical locations and may lead to far-reaching applications. As such, the focus is placed on research-derived educational and psycho-educative practices that seed success for students with intellectual disabilities in inclusive educational settings and the volume showcases new directions in theory, research, and practice that may inform the education and psychosocial development of students with intellectual disabilities globally.The chapter contributors in this volume consist of 31 scholars from ten different countries, and they come from a great variety of research areas (i.e., teacher education, educational psychology, special education and disability policy, special needs and inclusive education, health sciences). This volume, with a series of subsections, offers insights and useful strategies to promote meaningful advances for students with intellectual disabilities globally.